Analisis Hukum Penjatuhan Pidana Bersyarat dalam Tindak Pidana Pencurian Ringan: Studi Putusan Nomor 70/Pid.C/2025/PN Lbp - Josua Sembiring; Syahrul Bakti Harahap (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The crime of petty theft is a legal issue that demands a proportional and fair imposition of punishment. Article 364 of the Criminal Code, a colonial legacy, has had its value limit adjusted through Supreme Court Regulation Number 02 of 2012 to Rp 2,500,000.00. In Decision Number 70/Pid.C/2025/PN Lbp, the judge imposed a conditional sentence on the perpetrator of rubber sap theft valued at Rp 372,000.00. This study aims to analyze the legal regulation of petty theft, the judge's legal considerations in imposing a conditional sentence, and the conformity of the sentencing with the objectives of punishment and the sense of justice in society. The research method used is normative legal research with a statutory approach, supported by field research through interviews, analyzed qualitatively and descriptively. The results show that the regulation of petty theft under Article 364 of the Criminal Code in conjunction with Supreme Court Regulation Number 02 of 2012 provides legal certainty in classifying theft cases with small losses to be tried under expedited proceedings by a single judge without detention. The judge's legal considerations in imposing a conditional sentence are based on the fulfillment of all elements of Article 364 of the Criminal Code and the requirements of Article 14a paragraph (1) of the Criminal Code, taking into account the defendant's status as a first-time offender, the small value of the loss, and the modern sentencing paradigm oriented towards rehabilitation. The sentencing in this decision is in accordance with the objectives of modern punishment and the sense of justice in society, and has a strong constitutional foundation in the 1945 Constitution of the Republic of Indonesia. This study suggests reform of the value limit for petty theft, improved coordination among law enforcement officials, and optimization of the application of special conditions in conditional sentences.